38 Single centre experience with h.pylori eradication therapy. (5th April 2017) - Shahin, A; McNamara, D
Abstract : Background: Helicobacter pylori, is a gram-negative, microaerophilic bacterium usually found in the stomach and has been linked with chronic gastritis, gastric and duodenal ulcers, gastric cancer and MALT. An increasing resistance to antibiotics has resulted in changes in the recommended eradication therapy. The H.Pylori study group has recently updated the recommended eradication therapy. Aim: To study the compliance with the updated therapy for H.Pylori infection. Method: The prescriptions for triple therapy were collected and reviewed in compliance with the guidelines. The results of the follow-up Urea Breath Test following completion of eradication therapy were recorded and the rate of successful eradication was compared in the group of patients who were treated according to the new recommendations versus old recommendations. Results: The initial compliance with the new guidelines was 82%. Staff and junior doctor education have resulted in improvement in compliance rate. Conclusions: 1. Longer duration of therapy and more compliance with new guidelines has been associated with improved eradication therapy. 2. Confirming eradication of H.Pylori is an essential step in reducing and eliminating long term complications.